Pusat Modifikasi Mobil Di Pekanbaru Dengan Pendekatan Eko Arsitektur - Said Sidik Sijori; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Modification enthusiasts in Pekanbaru City car modification requires an integrated container. The Place with car garage complete the facilities and provide all automotive service information. In addition, Car Modification Center in Pekanbaru as modification services will have a positive impact modification enthusiasts. Car Modification Center in Pekanbaru expected to be a comfortable and attractive building, through the design of eco-architecture approach. Designing Car Modification Center in Pekanbaru using the paradigm of eco-architecture design principles through the logic of cultural and eco eco technic. The two logic is transformed and adopted into the region with a touch of eco-architecture design. The design method derived from the concept of modification. Results of these concepts derived from aspects of planning includes determining the theme of the design, analysis of the site and the environment, user analysis, analysis of the activities, program space needs, the pattern of the relationship between space, structural analysis, analysis of circulation, materials analysis and elaboration of the concepts in design Car Modification Center in Pekanbaru.Keyword: modification, eco Architecture, eco technic, eco cultural